An Ecological Approach to CSA Prevention: Integrating Bronfenbrenner’s Theory with Islamic Morals and SDGs 4, 5, and 16 - Hend Abdulrahman Mubarak; Sri Marmoah; Moh. Salimi (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study examined adults’ attitudes toward body safety education and sexual harassment awareness as two separate concepts in early childhood on CSA prevention, and the provision of these concepts through stories that align with Islamic principles and contribute to SDGs 4, 5, and 16. Theoretical framework: This study is grounded in four levels of Bronfenbrenner's Ecological Systems Theory by exploring the five dimensions that contribute to CSA prevention. Literature review: Most global stories on CSA prevention lack cultural adaptation for Eastern and Islamic communities. This study addresses the gap by focusing on integrating Islamic morals. Methods: This study is a mixed-methods descriptive cross-sectional study. In November 2025, data were collected online (N = 338) in Egypt, Indonesia and other nations utilising a 28-item structured questionnaire on a 5-point Likert scale and an optional open-ended question. Quantitative data were analysed using Jamovi and JASP Software for descriptive and inferential statistics, and qualitative data were analysed using thematic analysis. Results: The findings reveal that 87% (N = 294) of participants agree and strongly agree with the six factors that enhance the prevention of CSA. Qualitative data assessed on shared responsibility,18.40%, and integration of Islamic morals, 6.30%. Implications: This study highlights the capability of future story-based interventions to align with the Islamic perspective and global frameworks like SDGs to enhance child protection. Novelty: This study highlights the operationalisation of Bronfenbrenner’s theory to design Islamic stories as a CSA prevention in the Middle East and Southeast Asia.